The warm ISM in the Sgr A region: mid-J CO, atomic carbon, ionized atomic carbon, and ionized nitrogen line observations with the Herschel/HIFI and NANTEN2/SMART Telescopes. Issue Volume 9:Issue S303(2013) (22nd May 2014) - García, Pablo; Simon, Robert; Stutzki, Jürgen; Requena-Torres, Miguel; Güsten, Rolf; Fukui, Yasuo; Yamamoto, Hiroaki; Bertoldi, Frank; Burton, Michael; Bronfman, Leonardo; Ogawa, Hideo
Abstract: We present Herschel /HIFI sub-mm atomic carbon ([Ci ] 3 P 1 – 3 P 0 and [Ci ] 3 P 2 – 3 P 1 ), ionized carbon ([Cii ] 2 P 3/2 – 2 P 1/2 ), and ionized nitrogen ([Nii ] 3 P 1 – 3 P 0 ) line observations obtained in the frame of the Herschel Guaranteed Time HEXGAL (Herschel EXtraGALactic) key program (P. I. Rolf Güsten, MPIfR), and NANTEN2/SMART carbon monoxide (CO( J = 4 – 3)) observations of the warm gas around the Sgr A region. The spectrally resolved emission from all lines, and the corresponding line intensity ratios, show a very complex morphology. The determination of spatial and spectral (anti)correlation with known sources in the Sgr A region such as the Arched Filaments, NTF filaments, the Sickle, Quintuplet cluster, CND clouds, is ongoing work.